2020
DOI: 10.1155/2020/1059025
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Like to Make a Big Thing out of It”: A Qualitative Interview-Based Study Exploring Factors Affecting Whether Young People Tell or Do Not Tell Their Friends about Their IBD

Abstract: Inflammatory Bowel Disease (IBD) describes a group of conditions that includes Crohn’s disease and ulcerative colitis. Unlike some chronic conditions, to a greater or lesser extent, IBD is hidden from or invisible to others which enables concealment of the condition, especially when stigma is associated with the condition. Concealment or nondisclosure allows a means of identity management. Disclosure of a chronic condition is not a single event, and it is dependent on many factors. There is little literature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(86 citation statements)
references
References 47 publications
3
83
0
Order By: Relevance
“…Some young people in the current study concealed their IBD from friends, while others downplayed the seriousness of their condition. Limiting disclosure and explanations about the “gory detail” are aimed at both protecting their friends and minimising the risk of rejection [ 17 ], although a consequence of this could be limiting access to the support that close friends can offer. Friends with a better understanding of IBD and its implications could help sustain social support and potentially mitigate some of the impact of living with IBD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some young people in the current study concealed their IBD from friends, while others downplayed the seriousness of their condition. Limiting disclosure and explanations about the “gory detail” are aimed at both protecting their friends and minimising the risk of rejection [ 17 ], although a consequence of this could be limiting access to the support that close friends can offer. Friends with a better understanding of IBD and its implications could help sustain social support and potentially mitigate some of the impact of living with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…This connects to the work of Flynn et al [ 44 ] who found young people with a supportive network are better able to form reliable and compassionate friendships. Young people in our study described certain friendships as being closer and more meaningful since disclosure [ 17 ], possibly reflecting a type of posttraumatic growth, sometimes experienced by young people after trauma exposure [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with IBD experience potential challenges to their psychological well-being: the course of the disease is unpredictable, the treatment and management regimes frustrating. Patients talk about the symptoms of the disease often being embarrassing and socially limiting [3,11], which makes telling others about their condition difficult [12,13]. While there are few studies with adolescents and young adults (AYA) with IBD, those studies show high rates of anxiety and depression among that population [14].…”
Section: Ibd and Mental Healthmentioning
confidence: 99%
“…Fears of abdominal pain, bowel noises, faecal incontinence, and/or a bowel urgency in public mean many people with IBD withdraw from social interactions because they feel ashamed. IBD nondisclosure due to embarrassment is also a reported problem in the literature [13,26], but, because concealment of any condition is associated with reduced engagement with others [28], feelings of disconnection and negative affect are likely to be high among those with IBD because of social problems as much as they are to do with disease severity. Indeed, recent work by Roberts, Gamwell et al [29] showed that difficulty communicating about their illness to others was associated with thwarted belonging that was also linked to higher depression.…”
Section: Risk Factors For Poor Mental Health Among Aya With Ibdmentioning
confidence: 99%